2012
DOI: 10.4161/onci.19735
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A is a central regulator of lung tumor growth

Abstract: In a recent study we reported increased expression of IL-17A in the lung of patients with lung adenocarcinoma. Local blockade of IL-17A in the lung, in a model of lung cancer revealed enhanced anti-tumor immunity characterized by increased IFNγ, a diminished T-regulatory cell number and reduced tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
1
12
0
4
Order By: Relevance
“…Our data showing that IL-17 stimulated IL-6, IL-8 and VEGF expression in the A549 cell line are in accordance with numerous studies reporting that IL-17 augments IL-6203334, IL-8 and VEGF release35 in various types of non-tumour and tumour cells. With regard to lung cancer, IL-17 has been reported to induce IL-6 expression13 in A549 cells, and Numasaki M et al 7. have demonstrated that IL-17 increases IL-6 and IL-8 expression in A549, Sq-19 and LK-87 cells but that VEGF production is not altered in these three cell lines using ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showing that IL-17 stimulated IL-6, IL-8 and VEGF expression in the A549 cell line are in accordance with numerous studies reporting that IL-17 augments IL-6203334, IL-8 and VEGF release35 in various types of non-tumour and tumour cells. With regard to lung cancer, IL-17 has been reported to induce IL-6 expression13 in A549 cells, and Numasaki M et al 7. have demonstrated that IL-17 increases IL-6 and IL-8 expression in A549, Sq-19 and LK-87 cells but that VEGF production is not altered in these three cell lines using ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, IL-17 triggers tumour progression, mainly due to its proangiogenic properties by stimulating the production of angiogenic factors. Many cytokines, such as interleukin-6 (IL-6)13, interleukin-8 (IL-8)1415 and vascular endothelial cell growth factor (VEGF)16, are well-known angiogenic inducers, and IL-17 induces these cytokines in lung cancer. However, the mechanism by which IL-17 mediates the secretion of these angiogenic factors remains unclear.…”
mentioning
confidence: 99%
“…Th17 cells are a subtype of CD4 + T cells induced by different cytokines, such as IL‐6, TGF‐β1, IL‐23, IL‐21, and IL‐1β . They play an important role in the pathogenesis of several diseases, such as asthma, MS, and cancer . Th17 cells are involved in the induction of EAE, which resembles the early inflammatory phase of MS in humans .…”
Section: Discussionmentioning
confidence: 99%
“…The direct relationship between IL-17A and the increased risk of developing of numerous cancers, including NSCLC, has been demonstrated. On this basis it is considered as the central regulator of lung tumor growth [13]. Among other things, it promotes the migration and invasion of lung cancer cells via the NF-κB/ZEB1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%